Islamic Religious Education in the Merdeka Curriculum Era: A Systematic Literature Synthesis on Methods, Digital Media, and Educational Technology - Selvia Mei Ristian Prastiwi; Abdul Aziz; Ayus Ahmad Yusuf (Journal of Islamic Education Research, 2026)
The digital transformation of education has significantly influenced the implementation of the Merdeka Curriculum, particularly in Islamic Religious Education (Pendidikan Agama Islam [PAI]). This study aims to synthesize research findings on the transformation of PAI learning and develop an integrative conceptual model linking pedagogical innovation, digital media, educational technology, and Islamic character formation. Using a Systematic Literature Review (SLR) based on the PRISMA 2020 protocol, 25 Scopus- and Sinta-indexed journal articles published between 2021 and 2025 were systematically analyzed. The findings reveal that the Merdeka Curriculum encourages student-centered learning approaches, including Project-Based Learning (PjBL), Contextual Teaching and Learning (CTL), Flipped Classroom, and Blended Learning, supported by digital media and educational technologies such as Learning Management Systems (LMS), mobile learning, gamification, and artificial intelligence (AI). Teacher competence and digital ethics emerged as key mediating factors in the success of learning transformation. The originality of this study lies in the development of the Integrative Digital Islamic Learning Ecosystem Model (IDILEM), which integrates seven interconnected components and embeds Islamic technology ethics—tabayyun, maṣlaḥah, ‘adl, and amānah—into the TPACK and Connectivism frameworks through ETPACK. This study contributes a theoretical framework and practical guidance for designing digitally adaptive PAI learning while preserving Islamic values.